Left ventricular systolic function parameters are increased in patients with primary biliary cholangitis without cirrhosis. (4th February 2022) - Bidiuk, J; Styczynski, G; Szmigielski, CA; Lewandowski, J; Sinski, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Primary biliary cholangitis (PBC) is a chronic, autoimmune liver disease causing destruction of the small intralobular bile ducts in the liver. PBC patients can also develop extrahepatic manifestations, mostly related to skin, nervous system and laboratory abnormalities. Cardiac involvement is inconsistent in PBC studies despite high levels of serum lipids. Cardiac abnormalities are especially important because with the treatment many patients with early-stage PBC may have a normal life expectancy and therefore the cardiovascular complications can develop. Additionally, in recent years new echocardiographic modalities emerged letting for more precise analysis of cardiac morphology and function. Purpose: The purpose of the study was to compare novel and classic echocardiographic indices in patients with confirmed PBC without cirrhosis and in control subjects. Methods: 22 female patients with PBC and without cirrhosis and 44 healthy females, matched for age, (53.3 ± 9 years and 50.9 ± 8 years respectively, p = 0.065) were investigated. TTE study was performed and analysis of left ventricular (LV) global longitudinal strain (GLS) and myocardial work was performed. Results: Systolic blood pressure (SBP) differed between PBC and control group  (128 ± 17 mmHg and 116 ± 11 mmHg respectively, p = 0.006),  while diastolic blood pressure (DBP) (78 ± 10 mmHg and 76 ± 10 mmHg, p = 0.2) and heart rate (HR) (73 ± 12 bpm and 70 ± 8 bpm, p = 0.32) did not. PBC group had increased diameter of cardiac chambers when adjusted for body surface area (BSA), including left atrium (LA/BSA) and right ventricle (RV/BSA), as well as left ventricular mass (LWMI) and relative wall thickness (RWT) (Table) with no difference in left ventricular end diastolic diameter (LVEDD/BSA). LV ejection fraction (EF) measured by Simpson method was increased in PBC group (Table).  LV diastolic function parameters (E/A, E/e') were impaired in patients with PBC when compared with controls (Table 1). LV GLS indices (GLSAVG, GLSLAX, GLS4C, GLS2C) were significantly higher in PBC group, as well as global myocardial work indexes : global myocardial work (GWI) and global constructive work (GCW).  Global work efficiency (GWE) and global wasted work (GWW)  indexes were not different (Table). Conclusion: Our study shows that in patients with PBC without cirrhosis LV systolic function is increased. That implies hyperkinetic circulation in that group of patients even before the development of  cirrhosis.